ICT and Education for Refugees in Transit - Wahyuni, Dewi Sari; Fatdha, T Sy Eiva (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
Refugees in transit often have no access to formal education. Indonesia as one of transit countries has allowed these community school-age children to join public school. Unfortunately, teenagers and adults do not have similar consent. As most of them are stranded for a long time to skip their basic education, there should be a bridge so that they still can catch up with their secondary or even higher education level. During their uncertain waiting time, some international and national organizations and local institutions have provided them with private classes in specific subjects. The problem is these classes are unaligned with the lesson grade in host country formal education institution, which is categorized based on learners’ ages. Moreover, they are placed in separated places (detention centre, interception, community housings) which cost time and fare to get these refugees in one education centre. The alternative solution for handling this situation is by having blended learning, a combination of online learning platform and face-to-face meeting managed by teachers both from the host country and refugees. These students although they are limited by any means, have been familiar with ICT such as Microsoft Office, Photoshop, Multimedia and Internet. The online learning platform will muddle through time and distance in order to support them to take Package A, B, C (National Elementary, Junior and Senior High School Equivalency) tests as these tests are admitted at work and further study in host country as well as their destination countries without age limitation.